LASER ACUPUNTURA VERSUS ELETROACUPUNTURA PARA O CONTROLE DA DOR PÓS-OPERATÓRIA EM GATAS SUBMETIDAS À OVARIOSALPINGOHISTERETOMIA - Marques, Virgínia Ines Moreira (2015)
The aim of this study was to compare the effects of laser acupuncture and electroacupuncture on postoperative pain and analgesic requirements in cats. Thirty cats undergoing ovariohysterectomy were sedated with IM ketamine (5mg/kg), midazolam (0.5mg/kg) and tramadol (2mg/kg). Prior to induction of general anesthesia, the subjects were randomly distributed into three groups of ten cats each: LA: bilateral stomach 36 and spleen 6 acupoints were stimulated with an infrared laser; EA: bilateral stomach 36 and spleen 6 acupoints were stimulated with an electrical stimulus; Control: no acupuncture was applied. Anesthesia was induced with IV propofol (4mg/kg) and maintained with isoflurane/O2. Postoperative analgesia was evaluated by a blinded assessor at 0.5, 1, 2, 4, 8, 12, 18, and 24 h following extubation using the Dynamic Interactive Visual Analogue Scale and Multidimensional Composite Scale. Rescue analgesia was provided with IM tramadol (2mg/kg), and the pain scores were reassessed 30 min after the rescue intervention. If the analgesia remained insufficient, meloxicam (0.2 mg/kg IM, single dose) was administered. Data were analyzed using t-tests, the Mann-Whitney U test and Friedman test. P < 0.05 was considered significant. There were no significant differences among groups for demographic data or pain scores. Cats in the Control group received significantly more postoperative supplemental analgesia than the LA and EA groups (P = 0.026). In the contexts analyzed, both acupuncture techniques (LA and EA) reduced postoperative analgesic requirements in cats undergoing ovariohysterectomy.